Advancements in diagnosis and treatment of lung adenocarcinoma patients under ECMO support: a case series and comprehensive literature review - Xinyi Luo; Jie Zhang; Jieyi Pan; Lingbo Nong; Yin Xi; Xiaowen Xie; Ya Wang; Weiqun He; Xiaobo Chen; Changhao Zhong; Haibo Zhang; Xiaoqing Liu; et al. (Journal of Cardiothoracic Surgery)
Abstract This case series explores the use of veno-venous extracorporeal membrane oxygenation (VV ECMO) as a bridge to diagnosis and treatment in patients with suspected lung adenocarcinoma and severe respiratory failure refractory to conventional mechanical ventilation. We present three cases where ECMO support was initiated to facilitate further diagnostic evaluations, including lung biopsy and bronchoalveolar lavage fluid liquid biopsy, enabling the identification of actionable mutations and guiding targeted therapies. Two patients achieved significant clinical improvement and were successfully weaned from ECMO, while one patient experienced an unfavorable outcome due to a combination of uncontrolled tumor progression and hospital-acquired pneumonia. Our findings suggest that ECMO, traditionally considered a relative contraindication in advanced cancer, can be a valuable temporary support in carefully selected patients, allowing time for diagnosis and targeted treatment initiation. Furthermore, our experience highlights the feasibility and safety of performing lung biopsies under ECMO with appropriate anticoagulation management. This study emphasizes the importance of individualized decision-making and a multidisciplinary approach when considering ECMO for lung cancer patients, carefully weighing the risks of infection and disease progression to optimize patient outcomes.